Mothering Under Surveillance: Psychological Dimensions of Welfare Stigma in Low-Income Mothers - Binti Zulkifli, Nur Aisyah; Chaiyasit, Kittipong; Gong, Jiaowei (Psychology of Woman Journal, 2024)
Objective: This study aimed to explore the psychological dimensions of welfare stigma among low-income mothers in Thailand who are subject to institutional surveillance and conditional welfare support.Methods and Materials: Using a qualitative research design, this study employed semi-structured, in-depth interviews with 27 low-income mothers residing in urban and semi-urban areas of Thailand. Participants were purposively sampled based on their current receipt of state welfare benefits and were interviewed until theoretical saturation was reached. Interviews lasted between 60 and 90 minutes, were audio-recorded with consent, and transcribed verbatim in the original language. Data were analyzed thematically using NVivo software following Braun and Clarke’s six-step framework to identify key categories, subcategories, and recurring concepts related to mothers’ emotional experiences and identity formation in the context of welfare surveillance.Findings: Thematic analysis revealed four overarching categories: emotional burden of welfare surveillance, disrupted maternal identity, coping strategies and resistance, and structural and institutional barriers. Participants described chronic stress, shame, and emotional exhaustion resulting from bureaucratic scrutiny and moral judgment. Welfare surveillance disrupted their maternal identity, fostering feelings of inadequacy and fragmentation. Despite these pressures, mothers demonstrated resilience through selective disclosure, emotional regulation, and informal peer support. Institutional practices such as invasive inspections and rigid eligibility rules intensified mistrust and left psychological needs unmet. These findings align with existing international research on welfare stigma, while also highlighting context-specific emotional impacts within Thai welfare systems.Conclusion: Policies and practices must be restructured to prioritize dignity, reduce bureaucratic harm, and provide integrated emotional support to empower welfare-involved mothers and mitigate the long-term impact of stigma.